Southern Farmers' Attitudes and Opinions about Federal Conservation Programs and the 2007 Farm Bill - Michele C. Marra; Rodney L. Clouser; James L. Novak; Nathan B. Smith (EDIS)
FE682, an 8-page fact sheet by Michele C. Marra, Rodney L. Clouser, James L. Novak, and Nathan B. Smith, draws from the results of a national survey to report on southern farmers' attitudes and opinions about present and future conservation programs and goals. The information contained in this report should help policy makers make decisions that take the desires of farmers into consideration, and should also be of use to state Extension specialists and county agents in the southern region, in that it shows some areas where more farmer education might be beneficial. Includes references. Published by the UF Department of Food and Resource Economics, February 2007.